(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2017)
Background: Fistula formation is the most common complication with various rates among different techniques of hypospadias repair. The urethral advancement as an one stage technique for repair of hypospadias is considered a good technique. As no new urethral tube is constructed there is no risk of fistula. We assess the outcomes of the Limited Urethral Mobilization (LUM) technique in distal hypospadias repair. Methods: Our study included 20 patients aged upto 12 years who were treated with Limited urethral mobilization technique for distal hypospadias in Shaheed Suhrawardy Medical College Hospital from December 2014 to December 2015. The urethra proximal to the meatus was mobilized for a distance sufficient to allow it to reach the glans tip without tension. Then the urethra was placed in the glanular bed and glanular reconstruction was performed. Results: Three-fold urethral mobilization was sufficient for construction of tension-free urethra-glanular anastomosis. Cosmetically normal looking circumcised penis with ventrally slit meatus achieved in all but one subcoronal case where the most distal of the glans approximation sutures disrupted leading to a minor detachment in the glans. The minor complications includes preputial edema in one patient, two patients had wound infection, one had meatal stenosis which was treated with gentle dilatations. Postoperative urethro cutaneous fistula, retraction of the urethral meatus or recurrent chordee were not observed. Conclusion: Distal hypospadias repair with the LUM technique can be effective with satisfactory cosmetic and functional results. There is no chance for development of urethro cutaneous fistula, a major postoperative complication of other surgical techniques of creating a neourethra. Postoperative management is simple and a brief hospital stay is sufficient. Chatt Maa Shi Hosp Med Coll J; Vol.16 (1); Jan 2017; Page 37-41